Does transanal local resection increase morbidity for subsequent total mesorectal excision for early rectal cancer?. (30th October 2018) - Coton, C.; Lefevre, J. H.; Debove, C.; Creavin, B.; Chafai, N.; Tiret, E.; Parc, Y.
Abstract: Aim: Local excision is recommended for early rectal cancer (pT1). Complementary total mesorectal excision (cTME) is warranted when bad pathological features are present. The impact of a prior local resection on the outcome remains unclear. The aim of this study was to assess if prior local excision increases the morbidity of a subsequent cTME compared with primary TME. Methods: From 2001 to 2016 all patients who underwent TME after local excision for rectal adenocarcinoma were studied. All were matched (1:1) with patients who underwent primary TME, without neoadjuvant radiochemotherapy. The matching factors included age, sex, body mass index, American Society of Anesthesiologists score and type of surgery. Short‐term morbidity and pathological examination of the resected specimen were compared. Results: Forty‐one patients were included (14 women, 34%, mean age 65 ± 11 years), comprising classic transanal excision (66%) and transanal endoscopic microsurgery (34%), and were matched to 41 patients who had primary TME. cTME was significantly longer (315 min ± 87 vs 275 min ± 58, P = 0.03). The overall morbidity was 48.8% in the local excision group vs 31.7% in the control group ( P = 0.18). Surgical morbidity was 31.7% vs 26.8% ( P = 0.8). Anastomotic related morbidity was similar (local excision 17% vs TME 14.6%, P = 0.84) and the mean length of stay was similar (14 days) in both groups. There was a tendency to a worse quality of mesorectal excision in the cTME group (17% vs 5%, P = 0.15). Conclusion: Local excision prior to TME for early rectal cancer tends to increase overall morbidity and may worsen the quality of the mesorectal plane but should be considered as a surgical approach in select cases.